Microsurgical management of bronchogenic cysts in the thalamus: An illustrative case and literature review. (August 2014) - Wang, Jun; Guo, Zong-ze; Wang, Yun-Jie; Qiu, Bo; Xing, De-guang
Abstract Intracranial bronchogenic cysts are extremely rare. This is the first reported case of a bronchogenic cyst arising from the thalamus. Complete microsurgical resection was undertaken. A literature review was conducted to explore the etiologies, diagnostic approaches, and therapeutic strategies for this type of rare disease.